KUALITAS PEKTIN DARI KULIT JERUK KUOK DAN KULIT JERUK BERASTAGI - Sri Ayu Theresya; Farida Hanum Hamzah; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Oranges are a fruit that thrives in the tropics, the high production of citrus fruits causes orange peel to become one of the wastes that can be used as raw material for pectin which is needed in the food, cosmetic and pharmaceutical industries.  The purpose of this study was to obtain the best ratio of kuok orange peel and berastagi orange peel to the quality of the pectin produced.  This study used a non-factorial Completely Randomized Design (CRD) in which there were five treatments and three replications.  The treatments in this study consisted of: P1 (Kuok orange peel: Berastagi orange peel (100:0), P2 (Kuok orange peel: Berastagi orange peel (75:25), P3 (Kuok orange peel: Berastagi orange peel (50:50), P4 (Kuok orange peel: Berastagi orange peel (25:75), P5 (Kuok orange peel: Berastagi orange peel (0:100).  The data contained in this study were statistically analyzed using Analysis of Variance (ANOVA) and continued with a further test using Duncan’s Multiple Range Test (DMRT) at a level of 5%.  The results of this study showed that the ratio of kuok orange peel and berastagi orange peel had a significant effect on yield, moisture content, ash content, methoxyl content and jelly formation.  Selected in this study were P4 (Kuok orange peel: Berastagi orange peel (25:75) with a yield of 10,60%, water content 5,02%, ash content 1,75%, methoxyl content 9,40%, jelly formation 2,37 minutes. Keywords: Pectin, kuok orange peel, berastagi orange peel, jelly formation